Equity Returns in the Banking Sector in the Wake of the Great Recession and the European Sovereign Debt Crisis - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2012)
This study finds that equity returns in the banking sector in the wake of the Great Recession and the European sovereign debt crisis have been driven mainly by weak growth prospects and heightened sovereign risk and to a lesser extent, by deteriorating funding conditions and investor sentiment. While the equity return performance in the banking sector has been dismal in general, better capitalized and less leveraged banks have outperformed their peers, a finding that supports policymakers' efforts to strengthen bank capitalization.